Embedding and Chemical Reactivation of Green Fluorescent Protein in the Whole Mouse Brain for Optical Micro-Imaging - Gang, Yadong; Zhou, Hongfu; Jia, Yao; Liu, Ling; Liu, Xiuli; Rao, Gong; Li, Longhui; Wang, Xiaojun; Lv, Xiaohua; Xiong, Hanqing; Yang, Zhongqin; Luo, Qingming; et al. (Frontiers in Neuroscience, 2017)
Resin embedding has been widely applied to fixing biological tissues for sectioning and imaging, but has long been regarded as incompatible with green fluorescent protein (GFP) labeled sample because it reduces GFP fluorescence. Recently there reported resin-embedded GFP-labeled brain tissue can provide bright three-dimensional, high-resolution imaging as embedded GFP molecules are only protonated rather than denatured and can be recovered to be fluorescent state (Xiong, H. et al. Nature Communications 5, 2014). Here we describe an optimized protocol for resin embedding and chemical reactivation of fluorescent protein labeled brain tissue, where mouse is used as experiment model, but the protocol can be applied to other species. We demonstrated how to reliably realize whole brain embedding and chemical reactivation of the fluorescent signal in resin-embedded tissue. The whole brain embedding process takes a total of 7 days. The duration of chemical reactivation is approximately 2 min for penetrating 4 μm in depth below the surface in the resin-embedded brain. This kind of sample can be observed using various fluorescence microscopies including commercial wide-filed, confocal and two-photon microscopy. Fine structures labeled with GFP across a whole brain can be detected after processing by this protocol. This protocol provides an efficient way to embed fluorescent protein labeled sample for optical imaging.